PENGARUH PELAYANAN, HARGA SERTA CARA PEMASARAN TERHADAP PENJUALAN TOKO EMAS REJEKI KEDIRI - Rohma, Miptaqul; Rosanita Purbaya, Gabriela (JUMBA (Jurnal Manajemen, Bisnis, dan Akuntansi), 2022)
From the results of this study it aims to determine the service in sales at the Rejeki Kediri gold shop which is very influential because good service can provide a sense of comfort to consumers. For the second hypothesis, it is rejected because prices do not affect sales, price fluctuations do not significantly affect existing sales, which affect sales, namely certain conditions such as inflation and the Covid-19 pandemic, in accordance with the shop owner's statement that prior to the Covid-19 pandemic sales the average shop is 35 million/day, during the covid-19 pandemic shop sales decreased by 43%, so the average value of sales during covid-19 was 10 million/day to 15 million/day. For the third hypothesis, it is accepted because good marketing to consumers will create a separate attraction so that consumers are willing to buy gold products from the Rejeki Kediri store, so that they can increase existing sales. This study used primary and secondary data analysis methods, while the data analysis used in this study was descriptive qualitative data analysis.